2007
DOI: 10.1086/518040
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the Host’s Iron Status on Tuberculosis

Abstract: Several lines of evidence have suggested that iron is critical for Mycobacterium tuberculosis growth in macrophages. Macrophage iron loading in patients with African iron overload increases the risk of tuberculosis (TB) and may worsen TB outcome. Likewise, macrophage iron loading may contribute to an increased predisposition toward TB in HIV infection. Human genetic disorders or variations may increase the risk of TB or worsen its outcome through macrophage iron loading, including the haptoglobin 2-2 phenotype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
131
2
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(143 citation statements)
references
References 78 publications
6
131
2
3
Order By: Relevance
“…These findings should also be considered in light of numerous reports that associate high serum iron levels and transferrin-iron saturation with an increased mortality and morbidity due to tuberculosis [16][17][18][19][20] . It is possible that extracellular M.tb present in a transferrin-rich environment utilize this pathway for immediate access to iron.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…These findings should also be considered in light of numerous reports that associate high serum iron levels and transferrin-iron saturation with an increased mortality and morbidity due to tuberculosis [16][17][18][19][20] . It is possible that extracellular M.tb present in a transferrin-rich environment utilize this pathway for immediate access to iron.…”
Section: Discussionmentioning
confidence: 84%
“…Other studies have demonstrated that ironsaturated transferrin promotes the replication of M. avium within the phagosome 15 . Elevated serum iron and high levels of ironsaturated transferrin are known to have a strong correlation with the exacerbation of tuberculosis in both mouse models and patient studies 3,[16][17][18][19][20] .…”
mentioning
confidence: 99%
“…Iron-deficiency anemia is a typical symptom observed in individuals heavily infected with hookworm, but rarely seen in those with other helminths. Iron status also affects TB disease; for example, iron overload is reported to be a risk for TB progression [25]. In this study, the MCV and MCHC of the students, which are indicators of iron-deficiency anemia, were lower than the standard values generally, but there was no difference between hookworm-infected and non-infected children (MCV: p=0.35; MCHC: p=0.47), and there was no difference in iron status between responders to ESAT6 and/or CFP10 and non-responders (p=0.16).…”
Section: Il-10mentioning
confidence: 99%
“…Most micro-organisms need a substantial amount of iron to ensure their survival and are endowed with various mechanisms and molecules to obtain iron from host ferroproteins such as haemoglobin, ferritin and transferrin (Ganz, 2009). For infections, such as tuberculosis, increased macrophage iron is associated with more severe infections with worse outcomes (Boelaert et al, 2007). Whereas, supplementing with iron can result in susceptibilty to malaria infections in areas with endemic malaria (Prentice, 2008).…”
Section: Acute Phase Response Inflammatory Response and Ferritinmentioning
confidence: 99%